Sentimental Education. Sound and Silence at History Museums - de Jong, Steffi (Museum and Society, 2018)
Using an interdisciplinary approach, this article analyses the uses of sound and silence in three Polish history museums: POLIN – Museum of the History of Polish Jews, the Warsaw Rising Museum and the Historical Museum of the City of Krakow’s exhibition Krakow under Nazi Occupation 1939-1945. It argues that in these museums sounds and silence serve a sentimental education. They are used both to transmit historical knowledge in a sensorial way and to affectively engage visitors. Diegetic sounds thereby generally serve the transmission of historical knowledge, whereas non-diegetic sounds are used as affective triggers. In tis way, a sonic immersion is achieved that induces visitors to feel as if they were in the past as well as inviting them to emotionally engage with this past.